2007
DOI: 10.1111/j.1468-3083.2007.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Telediagnosis and face‐to‐face diagnosis reliability for melanocytic and non‐melanocytic ‘pink’ lesions

Abstract: Our results underline that teledermoscopy of 'pink' lesions does not provide a similar degree of diagnostic accuracy as otherwise in face-to-face diagnosis perhaps due to the absence of typical criteria. Atypical skin lesions are characterized by the absence of typical dermoscopic patterns, and their teleconsultation does not always increase the diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…Motivated by the documented successes of teledermatology [11,14,15,16,17,18,19,20,21,22,23,24], by recent advances in the image quality of mobile-phone cameras, by the high rates of mobile-phone ownership within Australia, and by high rates of melanoma self-detection [25], here we investigate the practicality and utility of a novel clinical tool, the implementation of which has the ultimate aim of increasing the rates of early detection of melanoma: the remote diagnosis of melanocytic lesions using patient-generated clinical images obtained by mobile-phone cameras. Our hypothesis is that patient-motivated remote diagnosis of melanocytic lesions could be a viable alternative to conventional patient-motivated face-to-face (FTF) assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the documented successes of teledermatology [11,14,15,16,17,18,19,20,21,22,23,24], by recent advances in the image quality of mobile-phone cameras, by the high rates of mobile-phone ownership within Australia, and by high rates of melanoma self-detection [25], here we investigate the practicality and utility of a novel clinical tool, the implementation of which has the ultimate aim of increasing the rates of early detection of melanoma: the remote diagnosis of melanocytic lesions using patient-generated clinical images obtained by mobile-phone cameras. Our hypothesis is that patient-motivated remote diagnosis of melanocytic lesions could be a viable alternative to conventional patient-motivated face-to-face (FTF) assessments.…”
Section: Introductionmentioning
confidence: 99%
“…[16] There have been various studies which have demonstrated the effectiveness of teledermoscopy vis-à-vis face-to-face consultation, especially in the case of melanomas. [17,18] The same applies for the extended use of telepathology in conjunction with teledermatology. [19] The increased and more effective use of mobile devices like cell phones and personal digital assistants (PDAs) is another direction t o w a r d s w h i c h t e l e d e r m a t o l o g y i s expanding.…”
Section: Disadvantagesmentioning
confidence: 99%
“…Fabroccini et al 39 investigated the concordance between clinical and dermoscopic diagnosis of teledermatology and FTF consultation to histopathologic diagnosis and found that telediagnosis presented lesser agreement than FTF diagnosis (kappa 0.44-0.45 vs 0.52-0.70). The interobserver agreement between the two teledermatologists was fair for clinical diagnosis (kappa 0.36) and moderate (kappa 0.44) for dermoscopic diagnosis.…”
Section: Study Qualitymentioning
confidence: 99%
“…The interobserver agreement between the two teledermatologists was fair for clinical diagnosis (kappa 0.36) and moderate (kappa 0.44) for dermoscopic diagnosis. 39 Ferrer et al compared the concordance of telediagnosis and FTF diagnosis to the final diagnosis, after presential consultation with all complementary examinations. Teledermatology showed an agreement higher than FTF diagnosis, achieving an almost perfect level (kappa 0.95 vs 0.60).…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation